Complementary inverters based on low-dimensional semiconductors prepared by facile and fully scalable methods. (12th February 2019) - Kim, Bongjun; Pak, Sangyeon; Choi, Hyung Woo; Choi, Youngjin; Jang, A-Rang; Lee, Juwon; Chun, Young Tea; Cha, SeungNam; Sohn, Jung Inn
Abstract: Two-dimensional (2D) semiconductors offer great potential in nanoelectronics due to their unique electrical and optical properties mainly attributed to their atomically thin nature. To make use of 2D semiconductors for practical applications, it is highly desired to develop scalable methods for integration of complementary circuits rather than a discrete device. We report a simple, scalable method for fabricating complementary inverters based on n-type monolayer MoS2, grown by a chemical vapor deposition (CVD), and inkjet-printed p-type SWCNTs. The CVD and inkjet printing methods are effectively combined to show the feasibility in terms of the integration of low-dimensional materials for complementary circuits. In the complementary circuits, cost-effectively printed Ag is utilized as the source and drain electrodes for both MoS2 and SWCNT transistors. Both the n- and p-type transistors show decent device characteristics at low operating voltages under ambient conditions. As a result, the complementary inverter composed of MoS2 and SWCNT transistors exhibits excellent performance with a gain over 10, low power dissipation, high noise margins, and switching threshold of 1/2 V DD at a low operating voltage. This successful demonstration of the complementary inverter, the most basic building block in digital circuits, will lead promising 2D semiconductors to practical applications.